A short-term transition from a high-fat diet to a normal-fat diet before pregnancy exacerbates female mouse offspring obesity - Fu, Q; Olson, P; Rasmussen, D; Keith, B; Williamson, M; Zhang, K K; Xie, L (International Journal of Obesity, 2016)
Background/Objectives: Recent findings have highlighted the detrimental influence of maternal overnutrition and obesity on fetal development and early life development. However, there are no evidence-based guidelines regarding the optimal strategy for dietary intervention before pregnancy. Subjects/Methods: We used a murine model to study whether switching from a high-fat (HF) diet to a normal-fat (NF) diet (H1N group) 1 week before pregnancy could lead to in utero reprogramming of female offspring obesity; comparator groups were offspring given a consistent maternal HF group or NF group until weaning. After weaning, all female offspring were given the HF diet for either 9 or 12 weeks before being killed humanely. Results: H1N treatment did not result in maternal weight loss before pregnancy. NF offsprings were neither obese nor glucose intolerant during the entire experimental period. H1N offsprings were most obese after the 12-week postweaning HF diet and displayed glucose intolerance earlier than HF offsprings. Our mechanistic study showed reduced adipocyte insulin receptor substrate 1 (IRS1) and hepatic IRS2 expression and increased adipocyte p-Ser 636/639 and p-Ser 612 of H1N or HF offspring compared with that in the NF offspring. Among all groups, the H1N offspring had lowest level of IRS1 and the highest levels of p-Ser 636/639 and p-Ser 612 in gonadal adipocyte. In addition, the H1N offspring further reduced the expression of Glut4 and Glut2, vs those of the HF offspring, which was lower compared with the NF offspring. There were also enhanced expression of genes inhibiting glycogenesis and decreased hepatic glycogen in H1N vs HF or NF offspring. Furthermore, we showed extremely higher expression of lipogenesis and adipogenesis genes in gonadal adipocytes of H1N offspring compared with all other groups. Conclusions: Our results suggest that a transition from an HF diet to an NF diet shortly before pregnancy, without resulting in maternal weight loss, is not necessarily beneficial and may have deleterious effects on offspring.